A KSA system for competency-based assessment of clinicians' professional development in China and quality gap analysis. Issue 1 (31st December 2022) - Huang, Xiaoqing; Li, Zihua; Wang, Jiali; Cao, Endong; Zhuang, Guiying; Xiao, Fei; Zheng, Caihua; Zhang, Xiaowen; Chen, Man; Gao, Liqing; Guo, Pi; Lin, Peiwei; et al.
ABSTRACT: Background: We aim to create a holistic competency-based assessment system to measure competency evolution over time – one of the first such systems in China. Method: Two rounds of self-reported surveys were fielded among the graduates from the Shantou University Medical College: June through December 2017, and May through August 2018. Responses from three cohorts of graduates specializing in clinical medicine – new graduates, resident physicians, and senior physicians – were analyzed. Gaps between respondents' expected and existing levels of competencies were examined using a modified service quality model, SERVQUAL Results: A total of 605 questionnaires were collected in 2017 for the construction of competency indicators and a 5-level proficiency rating scale, and 407 in 2018, for confirmatory factor and competency gap analysis. Reliability coefficients of all competency indicators (36) were greater than 0.9. Three competency domains were identified through exploratory factor analysis: knowledge (K), skills (S), and attitude (A). The confirmatory factor analysis confirmed the fit of the scale (CMIN/DF < 4; CFI > 0.9; IFI > 0.9; RMSEA ≤ 0.08). Within the cohorts of resident and senior physicians, the largest competency gap was seen in the domain of knowledge (K): −1.84 and −1.41, respectively. Among new graduates, the largest gap was found in the domain of skills (S) (−1.92), with the gap in knowledge (−1.91) trailing closely behind. Conclusions: A competency-based assessment system is proposed to evaluate clinician's competency development in three domains: knowledge (K), skills (S), and attitude (A). The system consists of 36 competency indicators, a rating scale of 5 proficiency levels, and a gap analysis to measure competency evolution through 3 key milestones in clinician's professional career: new graduate, resident physician, and senior physician. The competency gaps identified can provide evidence-based guide to clinicians' own continuous development as well as future medical curriculum improvements.